Question

7. Solve for \( x \) and \( y \) given that: a) \( \quad(x+i y)(4 i)=8 \) b) \( \quad-\frac{1}{x+i y}+\frac{1}{1+3 i}=1 \) c) \( \frac{x}{1+i}-\frac{y}{2-i}=\frac{1-5 i}{3-2 i} \)

Ask by George Valdez. in Zambia
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\( x = 0 \) and \( y = -2 \).

Solution

### Problem 7.a We need to solve for real numbers \( x \) and \( y \) in the equation: \[ (x + i y)(4i) = 8 \] **Step 1:** Expand the left-hand side: \[ (x + i y)(4i) = 4i x + 4i^2 y = 4i x - 4 y \] (Note that \( i^2 = -1 \)) **Step 2:** Equate the real and imaginary parts to the right-hand side, which is \( 8 + 0i \): \[ \begin{cases} -4y = 8 \quad \text{(Real part)} \\ 4x = 0 \quad \text{(Imaginary part)} \end{cases} \] **Step 3:** Solve the equations: \[ \begin{cases} -4y = 8 \Rightarrow y = -2 \\ 4x = 0 \Rightarrow x = 0 \end{cases} \] **Answer:** \[ \boxed{x = 0,\ y = -2} \]

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Mind Expander

Let's tackle each equation one by one. ### a) Solve \( (x + i y)(4 i) = 8 \) First, expand the expression: \[ (4i)(x + i y) = 4ix - 4y \] This gives us: \[ 4ix - 4y = 8 \] Now, equate the real and imaginary parts. On the left side, the real part is \(-4y\) and the imaginary part is \(4x\), while on the right side, the real part is \(8\) and there is no imaginary part (0): 1. \( -4y = 8 \) 2. \( 4x = 0 \) From equation 1: \[ y = -2 \] From equation 2: \[ x = 0 \] Thus, the solution for part (a) is: \[ (x, y) = (0, -2) \] ### b) Solve \( -\frac{1}{x + i y} + \frac{1}{1 + 3i} = 1 \) First, simplify \( \frac{1}{1 + 3i} \) by multiplying the numerator and denominator by the conjugate: \[ \frac{1}{1 + 3i} \cdot \frac{1 - 3i}{1 - 3i} = \frac{1 - 3i}{1 + 9} = \frac{1 - 3i}{10} = \frac{1}{10} - \frac{3}{10}i \] Now, substitute this back into the equation: \[ -\frac{1}{x + iy} + \left(\frac{1}{10} - \frac{3}{10}i\right) = 1 \] Rearranging it gives: \[ -\frac{1}{x + iy} = 1 - \frac{1}{10} + \frac{3}{10}i = \frac{9}{10} + \frac{3}{10}i \] Next, taking the negative and moving terms gives: \[ \frac{1}{x + iy} = -\left(\frac{9}{10} + \frac{3}{10}i\right) \] To find \( x + iy \), take the reciprocal: \[ x + iy = \frac{1}{-\frac{9}{10} - \frac{3}{10}i} \] Multiply by the conjugate: \[ x + iy = \frac{-\frac{9}{10} + \frac{3}{10}i}{\left(-\frac{9}{10}\right)^2 + \left(-\frac{3}{10}\right)^2} = \frac{-\frac{9}{10} + \frac{3}{10}i}{\frac{81}{100} + \frac{9}{100}} = \frac{-\frac{9}{10} + \frac{3}{10}i}{\frac{90}{100}} = \frac{-9 + 3i}{90} = -\frac{1}{10} + \frac{1}{30}i \] Thus, we have: \[ x = -\frac{1}{10}, \quad y = \frac{1}{30} \] So, the solution for part (b) is: \[ (x, y) = \left(-\frac{1}{10}, \frac{1}{30}\right) \] ### c) Solve \( \frac{x}{1+i} - \frac{y}{2-i} = \frac{1-5i}{3-2i} \) First, simplify the right side. Multiply the numerator and denominator by the conjugate: \[ \frac{1-5i}{3-2i} \cdot \frac{3 + 2i}{3 + 2i} = \frac{(1-5i)(3+2i)}{(3)^2 + (2)^2} = \frac{3 + 2i - 15i - 10}{9 + 4} = \frac{-7 - 13i}{13} = -\frac{7}{13} - i \] Next, solve the left side separately: \[ \frac{x(2-i)}{(1+i)(2-i)} - \frac{y(1+i)}{(2-i)(1+i)} = -\frac{7}{13} - i \] The denominator simplifies to: \[ (1+i)(2-i) =

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy